An investigation of the effect of accounting controls, budget goal clarity, mental model implementation on accountability of government performance - Enny Susilowati Mardjono; Emrinaldi Nur DP (Universitas Hayam Wuruk Perbanas, 2015)
The research examines the effect of budget goal clarity and accounting control on dependent variable with Mental Model as mediating variable on accountability of city government performance. This research used sample consisting of 66 employees in The Finance Division of City Government Semarang that were managing income and expenditure of state budget (APBD), selected by means of judgment sampling. The hypothesis testing was done by using Warp Partial Least Square 3.0. The partial result of the research indicated, the budget goal clarity, accounting control are factor that affect positively on Accountability of City Government Performance. Simultaneously, it indicated Mental model didn’t mediate the relationship between budget goal clarity and accounting control toward accountability of city government performance. Yet, budget goal clarity and accounting control as partial impact to Mental Model. The positive result in budget goal clarity gives the impact for city of government to apply budget stated clearly and specifically. Accounting Control system should be used to facilitate the planning and supervision of the organization. Mental model of the operational officers do not reflect operational processes in various environments. This is due to the fact that most of the budget has been set with the existing systems that is standardized by LAKIP, so it cannot be flexible adjustment in various environments.